Characterizing the extractable proteins from tomato leaves – A proteomics study - Marietheres Kleuter; Yafei Yu; Lukas Verdegaal; Francesco Pancaldi; Antoine H.P. America; Atze Jan van der Goot; Luisa M. Trindade (Food Chemistry: X)
The ambition to utilize agricultural by-products has spotlighted tomato leaves as a promising source for plant-based proteins. High-yielding protein extractability is key for its industrial use, but previous studies reported decreased protein extractability at later stages of plant development. This study investigated the underlying factors in protein extractability through a comprehensive proteomics analysis across four plant developmental stages (vegetative, flowering, fruit-forming, mature-fruit). The findings linked reduced yields to a shift in leaf function, from anabolic to catabolic processes and (a)biotic stress responses. This functional shift is accompanied by decreased protein synthesis and increased protein degradation, leading to an overall decrease of the soluble protein fraction. Furthermore, incomplete extraction of soluble proteins from leaves of later developmental stages, suggested the presence of inhibitory molecules hindering the extraction process. These findings indicate that breeding strategies towards increased amounts of soluble proteins and reduced concentration of inhibitory molecules could enhance protein extraction yields.